11x+13=7x+41

Simple and best practice solution for 11x+13=7x+41 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x+13=7x+41 equation:


Simplifying
11x + 13 = 7x + 41

Reorder the terms:
13 + 11x = 7x + 41

Reorder the terms:
13 + 11x = 41 + 7x

Solving
13 + 11x = 41 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
13 + 11x + -7x = 41 + 7x + -7x

Combine like terms: 11x + -7x = 4x
13 + 4x = 41 + 7x + -7x

Combine like terms: 7x + -7x = 0
13 + 4x = 41 + 0
13 + 4x = 41

Add '-13' to each side of the equation.
13 + -13 + 4x = 41 + -13

Combine like terms: 13 + -13 = 0
0 + 4x = 41 + -13
4x = 41 + -13

Combine like terms: 41 + -13 = 28
4x = 28

Divide each side by '4'.
x = 7

Simplifying
x = 7

See similar equations:

| -7(2x-4)+2=-14x+30 | | 5-3(x-7)=32 | | 5x^2/3-9x^1/3-2=0 | | 17(z-6)=70 | | px+y=5 | | 4x-7=4(x+9) | | 5x+5+9= | | 19=y-1 | | xp+y=5 | | 120-50=n | | 7(6x-3)=42x-21 | | 3x+4-5x=22(2x-3)+44-16x | | 2x-y=22 | | 2(x+9)-15=-3 | | -3(m-6)=18 | | 3*12+4=n | | -4(m-8)-7m=-4(1+2m) | | -3/17p=-8 | | 12-3/2y=14 | | n-2=-4 | | 1.50p/10= | | 2(4w-5+w)=90 | | -5x+3(-4x-11)=137 | | 2x+6+4x-3= | | Log[5]x^2=log[5]16 | | (4.5)18(x)=126 | | (H+6)(h-2)h=672 | | 0.6x+1.18=0.8x+6.18 | | -28=3x | | (4.5)18x=126 | | 132/11=n | | 0.25w+0.17f=80000 |

Equations solver categories